Case–Control Study on TNFRSF6B Gene Polymorphism and Susceptibility to Gastric Cancer in a Chinese Han Population - Gu X; Mao Z; Pan H; Zou C; Ding G; Fan Y (Dove Medical Press, 2020)
Xuyu Gu,1 Zhenwei Mao,2 Huiwen Pan,2 Chen Zou,2 Guowen Ding,2 Yu Fan2 1School of Medicine, Southeast University, Nanjing, Jiangsu 210009, People’s Republic of China; 2Cancer Institute, Affiliated People’s Hospital of Jiangsu University, Zhenjiang, Jiangsu 212002, People’s Republic of ChinaCorrespondence: Yu Fan; Guowen DingCancer Institute, Affiliated People’s Hospital of Jiangsu University, Zhenjiang, Jiangsu 212002, People’s Republic of ChinaEmail yuf111223@sina.com; dingguowen2013@163.comPurpose: To explore the relationship between rs2297440 and rs2297441 polymorphisms of TNFRSF6B gene and susceptibility to gastric cancer.Methods: A hospital-based case-control study was conducted. A total of 577 gastric cancer cases and 678 normal controls were recruited. Their genotypes were determined using the SnapShot method.Results: The smoking rate in the case group (34.49%) was higher than that in the control group (27.29%). For TNFRSF6B rs2297440, among people < 62 years old, the risk of gastric cancer in TC people was 1.84 times that in TT people. Among the non-drinking people, the risk of gastric cancer in the CC type was 0.66 times that in the TT+TC type. Among the drinking population, the risk of gastric cancer in the TC type was 1.67 times that in the TT type, and the risk in the TC+CC type was 1.70 times that in the TT type. As for TNFRSF6B rs2297441, in males and non-drinkers, the risk of gastric cancer in the AG type was less than that in the GG type. No matter how old the patient is, the risk of gastric cancer in the AA type was less than that in the AG+GG type.Conclusion: A correlation exists between smoking and gastric cancer. For TNFRSF6B rs2297440, the TC genotype may be a risk factor for gastric cancer in people < 62 years old. In the non-drinking population, the homozygous mutant of CC may be a protective factor for gastric cancer. In the drinking population, TC type may be a risk factor, whereas the TC+CC type dominated by C may be a protective factor. For TNFRSF6B rs2297441, the AG genotype may be a risk factor for gastric cancer in males and non-drinkers. The AA homozygous mutant may be a protective factor for gastric cancer.Keywords: gastric cancer, TNFRSF6B gene, single nucleotide polymorphism, rs2297440, rs2297441